KIT and PDGFRA mutations and survival of gastrointestinal stromal tumor patients treated with adjuvant imatinib in a randomized trial - Joensuu, Heikki; Wardelmann, Eva; Eriksson, Mikael; Reichardt, Annette; Hall, Kirsten Sundby; Schütte, Jochen; Cameron, Silke; Hohenberger, Peter; Sihto, Harri; Jost, Philipp J.; Lindner, Lars H.; Bauer, Sebastian; et al. (Clinical cancer research, 2023)
Limited data are available about the influence of KIT and PDGFRA mutations on overall survival (OS) of patients with gastrointestinal stromal tumor (GIST) treated with adjuvant imatinib.The Scandinavian Sarcoma Group XVIII/AIO multicenter trial accrued 400 patients with a high risk for GIST recurrence after macroscopically complete surgery between February 4, 2004, and September 29, 2008. The patients received adjuvant imatinib 400 mg/day for either 1 year or 3 years based on random allocation. We analyzed using conventional sequencing KIT and PDGFRA mutations centrally from 341 (85%) patients who had localized, centrally confirmed GIST, and correlated the results with recurrence-free survival (RFS) and OS in exploratory analyses.During a median follow-up time of 10 years, 164 RFS events and 76 deaths occurred. Most patients were re-treated with imatinib when GIST recurred. Patients with KIT exon 11 deletion or indel mutation treated with 3 years of adjuvant imatinib survived longer than patients treated for 1 year [10-year OS 86% versus 64%, respectively; HR, 0.34; 95% confidence interval (CI), 0.15-0.72; P = 0.007], and also had longer RFS (10-year RFS 47% versus 29%; HR, 0.48; 95% CI, 0.31-0.74; P < 0.001). Patients with KIT exon 9 mutation had unfavorable OS regardless of the duration of adjuvant imatinib.Compared with 1 year of imatinib, 3 years of adjuvant imatinib led to 66% reduction in the estimated risk of death and a high 10-year OS rate in the subset of patients with a KIT exon 11 deletion/indel mutation.